A Methods engineering study GTI Sportswear Corporation - Chiu, Lirie (College of Engineering, 1998)
GTI Sportswear Corporation, a 100 percent Filipino owned corporation, serves as a fully integrated textile company. GTI's involvement covers spinning, weaving, finishing, wholesaling and retailing. It has put decades of experience to become an industry leader, setting new standards for productivity, quality, efficiency, reliability and profitability. The product under study is Style 15320 Wrinkle Free Shorts. The following major problems are identified : - ineffective plant layout. Departments are not laid out according to the flow of operations causing delays. Lack of maintenance plan. Maintenance and updating of machinery in the plant is not a priority for the company. -Uneven Work Distribution in the Sewing Process. Some line operations take a relatively large amount of time to finish. Thus, a large work-in process exists in the sewing section. - Disorganization in the Sewing Process. The assignment of labeling is not permanent causing confusion among workers and delays in operations. - Delays in Assembly II Operations in the Sewing Process. Defective Waistbands lags Assembly II Operations. - Delays in Markings in the Cutting Process. Manual marking of pattern paper by workers before cutting consumes time causing delays. The group proposed the following recommendations. - A new plant layout design to facilitate an efficient flow of materials. This resulted in lesser distance traveled of garments. Also, time of delays is decreased. - Steps in the sewing process are rearranged and combined to solve unequal job loading. This improved the standard times of operations. - Roving In-line and Intermediate inspections are incorporated to regulate delays caused by defects in waistband production. Assigning of particular departments to do specific jobs to avoid misunderstandings on task designation.